MTAP deficiency is highly homogeneous in advanced, muscle-invasive urothelial carcinoma of the urinary bladder - Natalia Gorbokon; Katharina Teljuk; Viktor Reiswich; Florian Lutz; Sebastian Dwertmann Rico; Clara Lühr; Christian Bernreuther; Yaryna Klos Al Bunni; Cosima Völkel; Henning Plage; Maximilian Lennartz; Margit Fisch; et al. (Scientific Reports)
Abstract Complete expression loss of S-methyl-5′-thioadenosine phosphorylase (MTAP) is caused by homozygous 9p21 deletion and results in a critical vulnerability of cancer cells towards drugs targeting multiple different pathways. MTAP deficiency is common in urothelial cancer, but data on its intratumoral heterogeneity—a potential obstacle for targeted therapies—are lacking. To study the heterogeneity of MTAP expression loss and 9p21 deletions in advanced primary urothelial cancers of the urinary bladder, a tissue microarray (TMA) composed of five different tissue spots from different tissue blocks of 105 pT2-4 urothelial carcinomas was analyzed by immunohistochemistry (IHC) and fluorescence in-situ hybridization (FISH). In addition, all tumor containing blocks (1–15, average 6.4) from 41 consecutive pT2-4 carcinomas were analyzed by IHC. Complete absence of MTAP staining (MTAP deficiency) was seen in 34.2% of 385 interpretable TMA samples. All 80 samples with a complete MTAP expression loss and FISH data had a homozygous 9p21 deletion while there were no cases with homozygous deletions within 178 samples with retained MTAP expression (100% FISH/IHC concordance). On a patient level, there was a homogeneous MTAP deficiency in 33%, a heterogeneous MTAP deficiency in 1%, and a retained MTAP expression in 66% of the 98 tumors with at least three interpretable TMA samples. Among 41 consecutive pT2-4 carcinomas from which 1–15 (average 6.4) whole sections were analyzed, MTAP was homogeneously deficient in 34.1%, heterogeneously deficient in 4.9% and homogeneously retained in 61.0%. MTAP deficiency is mostly homogeneous in advanced urothelial carcinoma. MTAP IHC is a near perfect surrogate for the detection of homozygous 9p21 (MTAP) deletions. Drugs targeting MTAP deficiency could be highly useful in a relevant subset of invasive urothelial bladder cancers.